ALTERNATIVE ARCHITECTURE OF PASSIVE OPTICAL NETWORK - Mohd Zulkifli, Abdullah (Universiti Malaysia Sarawak (UNIMAS), 2009)
Three alternative architectures of Passive Optical Network (PON) are modeled using Optiwave version 6.0 simulation packages. In particular optical power budgetary analysis is carried out on three PON models utilized distinct network topologies in the access network. From the simulation the optimum distance and the highest number of Optical Network Unit (ONU) is determined and presented in graphical data. The different network sizes and dimensions are discussed in detail. Using this approach, several alternatives of PON architectures are constructed to provide various options to suit with distinct environmen